PENGEMBANGAN MEDIA PEMBELAJARAN ILMU PENGETAHUAN ALAM BERBASIS METODE MONTESSORI DI SEKOLAH DASAR - Tuti Umryaty; Asrori Asrori; Tahmid Sabri (Universitas Tanjungpura, 2021)
Abstract This study aims to produce natural science learning media based on the Montessori method. While specifics development objectives are (1) Producing elementary school science learning media based on the montessori method for grade VI students, and (2) Knowing the student’s responses to the use of elementary school science learning media based on the Montessori method for grade VI. The research method used by researchers is research into the development of R&D models with quantitative and qualitative data analysis techniques. Data collection was carried out using a questionnaire obtained from the validation questionnaire of Montessori media experts, subject matter experts and students. Questionnaire data from the Montessori media expert validation was 96% with a very decent category, material experts produced 94% with a very feasible category Positive responses from the student questionnaire were obtained 94% and included in the very feasible category. The products produced are props. Based on the results of the study, it can be concluded that the development of science learning media based on the Montessori method meets the criteria for use in grade VI public elementary schools 13 West Pontianak after being validated by experts and the questionnaire responses from teachers and students. Keyword: Development of natural Science Media, Montessori Methods.